Financial intermediaries and the macroeconomy: Evidence from a high-frequency identification - Pablo Ottonello; Wenting Song (Bank of Canada, 2022)
We provide empirical evidence of the causal effects of changes in financial intermediaries' net worth on the aggregate economy. Our strategy identifies financial shocks as high-frequency changes in the market value of intermediaries' net worth in a narrow window around their earnings announcements, based on US tick-by-tick data. Using these shocks, we estimate that news of a 1% decline in intermediaries' net worth leads to a 0.2% to 0.4% decrease in the market value of nonfinancial firms. These effects are more pronounced for firms with high default risk and low liquidity and when the aggregate net worth of intermediaries is low.
Keywords: E32; E44; E51; G01; G12; G21; G23; G24; G32; 330; Asset pricing; Business fluctuations and cycles; Credit and credit aggregates; Financial institutions; Financial markets; Financial system regulation and policies; Monetary and financial indicators